Pediatric diencephalic tumors: a constellation of entities and management modalities - Pinto, Soniya N.; Chiang, Jason; Qaddoumi, Ibrahim; Livingston, David; Bag, Asim (Frontiers in Oncology, 2023)
The diencephalon is a complex midline structure consisting of the hypothalamus, neurohypophysis, subthalamus, thalamus, epithalamus and pineal body. Tumors arising from each of these diencephalic components differ significantly in terms of biology and prognosis. The aim of this comprehensive review is to describe the epidemiology, clinical symptoms, imaging, histology, and molecular markers in the context of the 2021 WHO classification of central nervous system neoplasms. We will also discuss the current management of each of these tumors.